Phytoplankton Supplementation Lowers Muscle Damage and Sustains Performance across Repeated Exercise Bouts in Humans and Improves Antioxidant Capacity in a Mechanistic Animal - Sharp, Matthew; Şahin, Kazım; Stefan, Matthew; Orhan, Cemal; Gheith, Raad; Reber, Dallen; Wilson, Jacob (Mdpi, 2020)
The purpose of this study was to investigate the impact of antioxidant-rich marine phytoplankton supplementation (Oceanix, OCX) on performance and muscle damage following a cross-training event in endurance-trained subjects. Additionally, an animal model was carried out to assess the effects of varying dosages of OCX, with exercise, on intramuscular antioxidant capacity. Methods: In the human trial, endurance-trained subjects (average running distance = 29.5 +/- 2.6 miles x week(-1)) were randomly divided into placebo (PLA) and OCX (25 mg) conditions for 14 days. The subjects were pre-tested on a one-mile uphill run, maximal isometric strength, countermovement jump (CMJ) and squat jump (SJ) power, and for muscle damage (creatine kinase (CK)). On Day 12, the subjects underwent a strenuous cross-training event. Measures were reassessed on Day 13 and 14 (24 h and 48 h Post event). In the animal model, Wistar rats were divided into four groups (n= 7): (i) Control (no exercise and placebo (CON)), (ii) Exercise (E), (iii) Exercise + OCX 1 (Oceanix, 2.55 mg/kg/day, (iv) Exercise + OCX 2 (5.1 mg/kg/day). The rats performed treadmill exercise five days a week for 6 weeks. Intramuscular antioxidant capacity (superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px)) and muscle damage (CK and myoglobin (MYOB) were collected. The data were analyzed using repeated measures ANOVA andt-test for select variables. The alpha value was set atp< 0.05. Results: For the human trial, SJ power lowered in PLA relative to OCX at 24 h Post (-15%,p< 0.05). Decrements in isometric strength from Pre to 48 h Post were greater in the PLA group (-12%,p< 0.05) than in the OCX. Serum CK levels were greater in the PLA compared to the OCX (+14%,p< 0.05). For the animal trial, the intramuscular antioxidant capacity was increased in a general dose-dependent manner (E + Oc2 > E + Oc1 > E > CON). Additionally, CK and MYOB were lower in supplemented compared to E alone. Conclusions: Phytoplankton supplementation (Oceanix) sustains performance and lowers muscle damage across repeated exercise bouts. The ingredient appears to operate through an elevating oxidative capacity in skeletal muscle.
Keywords: phytoplankton; antioxidants; muscle damage; muscle recovery; muscle soreness